Conceptual understanding of high school students on plantae - Yasinta Choirina; Murni Ramli; Yudi Rinanto (Journal of Education and Learning (EduLearn), 2019)
Kingdom Plantae is a topic taught in Grade Tenth in Indonesia high school. The previous researchers have found misconceptions and difficulties in understanding the classification and the nomenclature system of Kingdom Plantae. Understanding basic concepts of Kingdom Plantae is important to study the more complex system of Plantae. This research was aimed to analyze the conceptual understanding of high school students on Plantae. The participants were 372 eleven graders who had studied Kingdom Plantae and selected randomly from eleven high schools in Surakarta, Indonesia. The diagnostic test four-tier consisting of 20 items. The instrument was to identify conceptual understanding. The instrument showed result on validity (mean = 1.00 and SD = 0.06) and reliability (0.46). The test showed that 10.5% students grouped as understand, and the rest varied as to False Negative (4.4%), False Positive (10.1%), Lack of Knowledge (45.6%), and Misconception (29.4%). Based on the results of the test, the students have misconceptions about monocots and dicots, the morphology of Anacardium occidentale, Musa sp., and Solanum tuberosum, classification of Anacardium occidentale. It was recommended to do detail examination of the reasons of low achievement in conceptual understanding of students.